Multiscale and multidisciplinary method for plant selection to design green urban and peri-urban areas - Burlando, Patrizia; Ferrante, Antonio; Vagge, Ilda (Frontiers in Horticulture, 2025)
The planning and design of urban and peri-urban green spaces necessitate careful consideration of various factors, encompassing climatic and agronomic parameters, botanical and eco-physiological characteristics of ornamental plants, and interactions between buildings and green elements. These green areas, along with their composition, play a crucial role in providing essential ecosystem services within urban environments. The process of designing and planning green spaces is a complex, multidisciplinary endeavor, involving professionals such as architects, agronomists, botanists, hydrologists, and civil engineers. The initial steps involve evaluating the area and its location and prioritizing environmental and municipal constraints in the analysis. The selection of plants is heavily influenced by soil and climate parameters. In cases where the area is already green, a meticulous assessment of each plant is essential to determine whether preservation or substitution is more appropriate. Upon completion of the site analysis, the design of the future green area must consider its environmental and social functions, potential ecosystem services, its role within the broader context, compositional aspects, and the judicious use of plant species and materials. This paper proposes a working method that is both multidisciplinary and multiscale, aiming to create sustainable, effective green areas that thrive even in challenging conditions linked to human impact and climate change.